A novel audio based human interaction proof for visually challenged users - Korrapolu, Rishi; Sai. N, Manoj; Rao.M, Kameshwara (International Journal of Engineering and Technology, 2018)
CAPTCHAs are strategies to recognize human clients and PC programs naturally. CAPTCHAs shield different sorts of online administrations from beast compel assaults and foreswearing of administration via programmed PC programs. Most CAPTCHAs comprise of mages with misshaped content. Shockingly, visual CAPTCHAs constrain access to the a huge number of outwardly hindered individuals utilizing the Web. Sound CAPTCHAs were made to fathom this openness issue. However the presently accessible sound CAPTCHAs have been broken with differing achievement, utilizing the shortcoming in the techniques utilized. Our system, presents the user with an interface that plays a song using instrumental music (nonvocal) randomly selected from some language of users choice. The user is then asked to kind the music composer and then the device estimates whether it is a human or no longer by means of analyzing the response. A person look at turned into conducted to research the overall performance of our proposed mechanism.